Equity financing intention of elderly care enterprises: Influence of institutional logic and operation mode - Zhao, Yiqi; Wei, Dong; Zhao, Xianfeng; Dong, Xianglan; Guo, Luzhi (Frontiers in Public Health, 2022)
China’s elderly population is expected to exceed 300 million and enter the stage of moderate aging during the 14th Five-Year plan period from 2021-2025. From elderly care enterprises’ sustainable development perspective, the supply of elderly care services would be unsustainable if enterprises suffer long-term losses. In the latter’s pursuit of high profits, the burden on consumers will increase. Equity financing of these enterprises is the key to achieving high-quality transformation and development by considering economic and social benefits. This study considers 20 well-known China-based elderly care enterprises as the research object. It uses a fuzzy set to explore system logic, operation mode, management performance, and attitude of elderly care enterprises toward investment through the qualitative comparative analysis method. The causal relationship between them is clarified—because before China’s endowment enterprise equity financing intention, it is important to explore the effective path of endowment enterprises’ equity financing. In the past, this helped Chinese elderly care enterprises actively cope with the trend of population aging, meet the needs of diversified and multi-level elderly care services, establish a sustainable development mode, and achieve high-quality transformation and development. The results show that (1) the operating performance of elderly care enterprises under the mode of public construction and private operation is poor (2) Elderly care enterprises driven by public welfare logic are more likely to achieve higher business performance (3) Elderly care enterprises driven by business logic are more willing to introduce investment when they have made profits.